Pengaruh Media Boneka Tangan dalam Pembelajaran Terhadap Motivasi dan Keterampilan Bercerita Siswa Kelas II SDIT Darul Ilmi Bengkulu Utara - Ayu Dwinata, Winda; Muktadir, Abdul; Widi Winarni, Endang (UNIB Press, 2025)
This research aims to analyze the influence of hand puppet media in learning on the motivation and storytelling skills of class II students at SDIT Darul Ilmi North Bengkulu. This research is a quasi experimental research with a quantitative approach. The data collection techniques used are observation, questionnaires and performance or practical tests. The instruments used in this research were questionnaire sheets, skills assessment sheets, and teaching modules/RPP. The data that has been collected is then analyzed quantitatively using the SPSS application. Based on the research results, it was found that the use of hand puppet media in learning Indonesian has a significant effect on aspects of learning motivation. This is shown by the average posttest result of filling out the learning motivation questionnaire in the control class being 151. Meanwhile, the average posttest result in the experimental class is 165. The use of hand puppets in Indonesian language learning also has a significant effect on students' storytelling skills. This is shown by the average posttest of storytelling skills in the control class of 74 and the average posttest in the experimental class of 83. The conclusion of this research is that there is a significant influence of hand puppet media on motivation and storytelling skills. Furthermore, there is a relationship between motivation and storytelling skills using hand puppets.